2003
DOI: 10.1002/adma.200390117
|View full text |Cite
|
Sign up to set email alerts
|

Percolative Mechanism of Aging in Zirconia‐Containing Ceramics for Medical Applications

Abstract: tion of an ethanolic suspension of microspheres produces a colloidal crystal film that is of controlled thickness and essentially single-crystalline. The concentration of microspheres in ethanol was chosen to obtain a nominal thickness of 15 sphere layers.The synthesis of monomers 1, 2, and 3 was performed using previously published protocols [15,16,19]. Briefly 1,1¢-dilithioferrocene, synthesized from ferrocene and n-butyl lithium with N,N,N¢,N¢-tetramethylethylenediamine as catalyst, was treated with a 1.3 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 18 publications
2
51
0
4
Order By: Relevance
“…27,35 This explanation might be true when the amount of alumina addition is high, 12,27,35,36 but it cannot explain the degradation kinetics in this study for Y-TZPs containing a small amount of alumina. The area of zirconia exposed to water should be smaller as the alumina fraction was increased from 0.25 wt.% to 2 and 5 wt.%, but 0.25 wt.% alumina had a higher degradation retarding effect than 2 and 5 wt.% of alumina addition, which had a comparable effect.…”
Section: Higher Amount Of Alumina Addition Did Not Mean Better Effectmentioning
confidence: 52%
“…27,35 This explanation might be true when the amount of alumina addition is high, 12,27,35,36 but it cannot explain the degradation kinetics in this study for Y-TZPs containing a small amount of alumina. The area of zirconia exposed to water should be smaller as the alumina fraction was increased from 0.25 wt.% to 2 and 5 wt.%, but 0.25 wt.% alumina had a higher degradation retarding effect than 2 and 5 wt.% of alumina addition, which had a comparable effect.…”
Section: Higher Amount Of Alumina Addition Did Not Mean Better Effectmentioning
confidence: 52%
“…Therefore, the alumina matrix grain size is the main factor in characterizing the wear resistance of the composite materials at these loads, as has been determined previously for alumina materials. 20 Pecharromán et al 21 using IR reflectance measurements have stablished that the percolation threshold of alumina/3Y-TZP composites is located at 16 vol.% for 3-YTZP. In the case of compositions above this percolation threshold (AL22TZY), the wear rate at relatively low contact pressure of 20 N (1.1 GPa) was found to be around two orders of magnitude higher than the ones corresponding to 14 and 7 vol.% zirconia content, and very similar to the one obtained at higher loads (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…15 However, it is clearly impossible to completely avoid the transformation in a material where zirconia is the main phase. 18 Moreover, it has been shown that the zirconia level should be lower than the percolation threshold (16 vol.%) to avoid ageing propagation from grain to grain. 18,19 At last, even under the percolation threshold, significant transformation level can be observed at the beginning of some ageing experiments.…”
Section: Introductionmentioning
confidence: 99%
“…18 Moreover, it has been shown that the zirconia level should be lower than the percolation threshold (16 vol.%) to avoid ageing propagation from grain to grain. 18,19 At last, even under the percolation threshold, significant transformation level can be observed at the beginning of some ageing experiments. 19 Zirconia aggregates are suggested to be responsible for this transformation, but no study assessed clearly this issue.…”
Section: Introductionmentioning
confidence: 99%